Reducing cardiovascular risk - are omega 3 fatty acids the solution? - Silldorff, Julia; Fura, Tomasz; Dudek, Marcin; Zaucha, Radosław; Felińska, Zuzanna; Iszczuk, Oliwia; Anczyk, Stanisław; Gajkiewicz, Magdalena; Zając, Małgorzata (Quality in Sport, 2024)
Introduction and objective Omega-3 fatty acids possess numerous physiological characteristics, including anti-inflammatory, lipid-lowering, antiarrhythmic, and antithrombotic effects. There has been an ongoing discussion about their potential positive effects on human health and the extent of their influence. In this review, we will explore the current understanding of how omega-3 fatty acids impact the development of cardiovascular diseases. Review methods A review of publications on the effects of omega 3 fatty acids was conducted using the PubMed platform. The main keywords used in the search were "omega 3 fatty acids" and "cardiovascular diseases". The search included a review of the latest scientific work on the effects of omega 3 fatty acids on the body. Abbreviated description of the state of knowledge Omega-3 fatty acids exhibit diverse molecular mechanisms that are beneficial in combating cardiovascular diseases. Reducing serum triglycerides is one of the ways in which omega 3 fatty acids have an advantageous effect on the cardiovascular system. Dietary sources and supplementation offer potential benefits. Summary Omega-3 fatty acids, including EPA and DHA, exhibit various molecular mechanisms such as antithrombotic, anti-inflammatory, and lipid-lowering effects, which are crucial in combating CVDs. Dietary sources of omega-3 include both animal and plant products. Supplementing with omega-3 fatty acids, particularly in patients with elevated triglyceride levels, can significantly reduce CVD risk factors and mortality rates. Recommendations suggest consuming 2 servings of fish per week or supplementing with DHA + EPA to support cardiovascular health. Despite some controversies in research findings, omega-3 supplementation remains beneficial. Ongoing research continues to explore the optimal use and efficacy of omega-3 fatty acids in cardiovascular health.